Effect of Alloying Elements on Properties and Structure of High Chromium Cast Irons - Záděra, A; Kaňa, V; Krutiš, V (Archives of metallurgy and materials, 2018)
The paper deals with hypereutectic high chromium cast irons. The subject of examination was the effect of various alloying elements (Ti, W, Mo, V) on the size of primary carbides and on the resultant material hardness. Using a scanning electron microscope with a wave dispersion analyser, the carbon content in carbides was established. To determine the other elements, an energy dispersion analyser was used. It was found that both the primary and the eutectic carbides were of the M7C3 type and very similar in composition. The carbides always contained Cr and Fe, and also W, Mo, V or Ti, in dependence on the alloying elements used. The structure of materials containing only chromium without any alloying additions exhibited coarse acicular primary carbides. The structure of materials alloyed with another element was always finer. Marked refinement was obtained by Ti alloying.